Development of RQANI Learning Modules to Improve Students' Understanding of concepts Class XI Science at SMA Negeri 6 Ternate City - Amin, Astuti Muh; Samsudin, Ningsih; Muna, Lintal (Universitas Lampung, 2023)
RQANI (Reading, Questioning, Answering, Elaboration, and Integration) is a learning model that integrates science and Islamic values. Utilizing modules in the learning process can provide learning opportunities for students to be more independent and motivated to master concepts. The research objectives were to identify (1) the validity of the RQANI module on body defense system material for class XI IPA students at SMA Negeri 6 Ternate City and (2) the effectiveness of the RQANI learning module in increasing students' understanding of concepts in class XI Science at SMA Negeri 6 Ternate City. This research is development research that refers to 4-D development design. The trial was carried out on a limited scale on class XI Science students at SMA Negeri 6 Ternate City. The instruments used in collecting research data consisted of validation sheets for research modules and instruments, response questionnaires, and essay tests to measure understanding of concepts. The research results showed (1) the validity of the RQANI-based learning module on body defense system material by the first validator in the very valid category (90.41) and the second validator in the valid category (79.16); (2) RQANI-based learning modules are effective in increasing concept understanding with 38.46% of students obtaining N-Gain at high criteria; and 38.46% of students gave very good responses and 53.84% of students gave good responses to the RQANI module. The research conclusion is that the learning module is declared valid and effective in increasing student understanding. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28919